A Literature Review of Net Profit Margin: - Wuku Astuti (Social Science Studies, 2021)
Net profit margin is one indicator of the company's financial performance. Net profit margin on cruise industries, for example, exhibit consistently robust growth trends for the leading cruise players, over 2016–2019, contrary to most commercial shipping market segments that experienced abrupt and persistent revenue declines since the outbreak of 2008 global financial crisis, cruise shipping has seen a robust resistance and relatively rapid recovery. Spurred by the growing importance of institutional investors, capital markets in emerging economies experience rapid growth. Specifically, equities ownership in emerging capital markets have tripled since the early 1990s. Another factor attracting equities investment involves institutional investors who offer potential for increased monitoring in the invested firms. The objective of this research is to determine the factors associated with net profit margin. I presented a literature study using systematic literature review of relevant publications and as a result of this process, 18 articles are included and then examined the bibliographical references to check the validity of the inquiry and to avoid any potential omissions. I identify several variables that affect and affected by net profit margin.